Nuclear receptors and other molecular targets in type 2 diabetes mellitus - Deepa Sugumar, Emdormi Rymbai, Soumya Vasu, Divakar Selvaraj (Journal of Applied Pharmaceutical Science, 2023)
Diabetes is a group of metabolic disorders characterized by chronic hyperglycemia and glucose intolerance. Diabetes occurs because of defects in insulin secretion, insulin action, or both. Type 2 diabetes mellitus (T2DM), with a prevalence of more than 95%, is the most prevalent form of diabetes. Over the years, the effectiveness of the drugs used to treat diabetes has reduced. For this reason, targeting newer molecular targets might lead to the effectiveness of drugs. Over the years, there has been a great interest in targeting nuclear receptors for the treatment of T2DM. Some of these targets have been applied at the clinical level. However, other molecular targets belonging to G-coupled protein receptors, enzymes, and kinases have also been explored. Hence, in this review, we will discuss a few potential targets that have been applied clinically or could be the target for the treatment of T2DM.